Differentiated and negotiable mechanism for data communication - Wenlong KOU; Fenghua LI; Xiuze DONG; Xiaogang CAO; Kui GENG; Qing LI (Tongxin xuebao)
In view of the massive and differentiated computing units and terminal devices in the cloud environment and the Internet of things, the differences in hardware resources and computing capabilities posed new challenges to high reliability and high performance data communication, a data communication mechanism supporting differentiation and negotiation was proposed.A parameters negotiation method was proposed, and parameters were negotiated by the sender according to the difference of the receiver capability to achieve differentiated and negotiable data communication.A retransmission feedback mechanism was designed, and the transmission rate was dynamically adjusted and the data was retransmitted based on the data reception feedback of the receiver by the sender to improve communication efficiency and reliability.The experimental results show that the proposed mechanism can perform dynamic adaptive, efficient and parallel communication according to the difference of the receiver capability.